Dual responsive mesoporous silica nanoparticles for targeted co-delivery of hydrophobic and hydrophilic anticancer drugs to tumor cells. Issue 25 (19th May 2016) - Chen, Xin; Liu, Zhongning
Abstract : Dual responsive mesoporous silica nanoparticles integrating stepwise tumor targeting and co-delivery of multiple anticancer drugs were developed to attenuate the drug resistance of cancer cells. Abstract : Dual responsive mesoporous silica nanoparticles (MSNs) integrating stepwise tumor targeting and co-delivery of multiple anticancer drugs were developed to attenuate the drug resistance of cancer cells (SCC cells). The nano-composite consists of MSNs as nanocarrier I for hydrophobic drugs delivery, generation 2 PAMAM dendrimer (PAMAM-G2) as nanocarrier II for hydrophilic drug delivery and hyaluronic acid (HA) as a tumor targeting agent, which effectively encapsulated drug molecules and blocked their outward diffusion from the mesopores of the MSNs before selective accumulation around the tumor. The responsive drug releases happened with cap (HA and PAMAM-G2) removal following tumor targeting and cell endocytosis, which was triggered by two intracellular stimuli, a low pH value (hydrophilic drug release) and glutathione (hydrophobic drug release). The highly selective particle-uptake by tumor cells and subsequent efficient drug co-delivery to these cells, which were directly demonstrated by fluorescence microscopy, resulted in a fourfold efficacy against tumor cells compared with normal cells, as well as higher tumor cytotoxicity than that caused by free drugs. These results indicate that this MSNs–dendrimer–HA construct, with performance of selective drug co-delivery and dual responsive drug release, could be a promising platform for cancer therapy.